Preventive detention and the presumption of innocence: A legal paradox in Peruvian criminal law? - Huamán, Hernán Yonathan Barragán (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the legal paradox between preventive detention and the presumption of innocence in Peruvian criminal law. Preventive detention is a precautionary measure of last resort, regulated by the New Code of Criminal Procedure (NCPP), designed to ensure the proper development of the criminal process. However, its frequent and sometimes arbitrary application raises concerns about its impact on fundamental rights. A qualitative research design was adopted, incorporating case law analysis, judicial files, and semi-structured interviews with 500 judges, prosecutors, trial lawyers, and detainees. The study focuses on preventive detention cases in Peru between 2018 and 2024, emphasizing high-profile cases and jurisprudential developments. The results reveal that while preventive detention does not inherently violate the presumption of innocence, its excessive or arbitrary use may turn it into a form of anticipated punishment. Factors such as media pressure, the perception of impunity, and the lack of alternative precautionary measures contribute to its recurrent application. Compared to other legal systems, Peru applies preventive detention for prolonged periods, exceeding international standards. The findings indicate that judicial reforms are necessary to ensure that preventive detention remains an exceptional measure, strictly adhering to proportionality and due process principles. Strengthening judicial safeguards and promoting alternative precautionary measures are crucial to upholding the presumption of innocence. The study provides valuable insights for policymakers, legal practitioners, and judicial authorities in refining preventive detention regulations, advocating for procedural reforms that balance public security concerns with human rights protections to guarantee the fair and proportional use of preventive detention in criminal proceedings.